The Collaboration Between Doctors, Nurses, and Pharmacists in Optimizing Medication Management for Cardiac Emergency Patients: Collaboration Between Doctors, Nurses, and Pharmacists in Optimizing Medication Management for Cardiac Emergency Patients - Andreas, Adikia (JURNAL KESMAS DAN GIZI (JKG), 2024)
Cardiac emergencies, such as acute myocardial infarction (IMA), acute heart failure, and severe arrhythmias, are conditions that require immediate intervention to save the patient's life.b Appropriate drug management in these situations plays a crucial role in stabilizing the patient's condition, reducing the risk of complications, and improving clinical outcomes. However, the effectiveness of drug therapy in emergencies depends not only on the selection of the right drug, but also on how it is comprehensively managed by a medical team consisting of doctors, nurses, and pharmacists. Collaboration between doctors, nurses, and pharmacists in medication management in cardiac emergency patients aims to improve the speed, safety, and effectiveness of therapy. Nurses administer medications and monitor patient response, pharmacists ensure proper dosing, prevent drug interactions, and provide education. Effective collaboration reduces the risk of medicationerrors, improves patient safety, and ensures optimal therapy through good communication and systematic coordination. Good collaboration between doctors, nurses, and pharmacists is essential in the medication management of cardiac emergency patients. With effective communication and good coordination, therapy can be delivered more quickly, safely, and optimally